2020
DOI: 10.1136/bmjopen-2019-029172
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate prescribing in dementia: a state-of-the-art review since 2007

Abstract: ObjectivesDementia frequently occurs alongside comorbidities. Coexisting conditions are often managed with multiple medications, leading to increased risk of potentially inappropriate medication and adverse drug reactions. We aimed to estimate prevalence of, and identify factors reported to be associated with, potentially inappropriate prescribing (PIP) for older individuals diagnosed with dementia.DesignWe used a state-of-the-art review approach, selecting papers written in English and published from 2007 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 59 publications
(80 reference statements)
2
37
0
Order By: Relevance
“…It is notable that the mean number of chronic medications used in the first year after diagnosis was as high as 22.89 per person-year and increased to 30.7 in the late stage of dementia, with an overall significant increasing trend. A high symptom burden in PwD may contribute to a greater need for medications; other risks such as multiple comorbidities, advanced age, depression, and a low functional status are also related to polypharmacy and potentially inappropriate medication (PIM) [26][27][28]. The number of prescribed medications is directly correlated to the risk of PIM among elderly patients with and without dementia [26,29].…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that the mean number of chronic medications used in the first year after diagnosis was as high as 22.89 per person-year and increased to 30.7 in the late stage of dementia, with an overall significant increasing trend. A high symptom burden in PwD may contribute to a greater need for medications; other risks such as multiple comorbidities, advanced age, depression, and a low functional status are also related to polypharmacy and potentially inappropriate medication (PIM) [26][27][28]. The number of prescribed medications is directly correlated to the risk of PIM among elderly patients with and without dementia [26,29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some conditions are common in old age but are not sufficiently recognised by clinicians, which eventually leads to underuse of the indicated medications [5, 6]. Certain people with dementia (PWD) who are considered underdiagnosed in typical primary practice [7] despite the constant increase in prevalence may be exposed to various health risks stemming from comorbidities [8-10] as well as adverse drug reactions, which are presumably induced by potential exposures to neuropsychiatric drugs [11, 12] or poor competence in their medication management. According to a survey implemented in 6 Japanese municipalities in 2012, the number of individuals with dementia in Japan was estimated to account for 15.7% of the entire older population.…”
Section: Introductionmentioning
confidence: 99%
“…In a Swedish study, 41% of acute hospitalizations of people with dementia were determined to be drug-related [14]. Nonetheless, PIM is widespread in people with dementia, with a prevalence ranging from 14-64% in a recent review [15].…”
Section: Introductionmentioning
confidence: 99%
“…In a Swedish study, 41%of acute hospitalizations of people with dementia were determined to be drug-related [ 14 ]. Nonetheless, PIM is widespread in people with dementia, with a prevalence ranging from 14–64%in a recent review [ 15 ]. In our previous study in Denmark, we found that 45%of people with dementia had filled at least one prescription for PIM in 2014 compared to 30%of people without dementia [ 16 ].…”
Section: Introductionmentioning
confidence: 99%